Extremely severe vitamin B12 deficiency : case presentation and review of literature = Ekstremno teška deficijencija vitamina B12 : prikaz slučaja i pregled literature - Pupić-Bakrač, Ana (Array, 2019)
Aim: Vitamin B12 (cobalamin) is nutrient from the vitamin B complex family. It is essential in the human body for deoxyribonucleic acid (DNA) synthesis and for cellular energy production. Vitamine B12 deficiency is decrease in its serum concentration below 220 pmol/L, and it can be present in various range of hematologic and systemic symptoms and signs. The aim of this article is to provide extensive information on extreme forms of deficiency of vitamin B12. Case report: 83-year-old men presented with fatigue, intolerance of physical activity, vertigo, paresthesia in fingers, dispersion, epigastric pain, vomitting and loss of apetite. Vital parameters were within normal range, and physical examination did not reveal any patological findings, except icterus of sclera and subicterus of skin. Urgent laboratory findings showed erythrocytes 1.18 x 1012/L (4.34-5.72 x 1012/L), hemoglobin 50 g/L (138-175 g/L), mean corpuscular volume (MCV) 123.6 fL (83.0-97.2 fL), vitamin B12 <61 pmol/L (220-665 pmol/L). Patient started parenteral therapy with vitamin B12. After 5 days, rapid increase in reticulocyte count was observed, with haemogram stabilization within 6 weeks. In a follow-up period of two years, the patient had no symptoms. Conclusion: We presented patient with extreme deficiency of vitamin B12. Screening for vitamin B12 deficiency should be established in each patient with macrocytic anemia, even with slightly elevated MCV.